Harnessing the Power of Community Conversations to Improve Transition Outcomes for Youth With IDD. (March 2018) - Molfenter, Nancy; Hartman, Ellie; Neugart, Jenny; Swedeen, Beth; Webb, Shannon; Roskowski, Matthew; Schlegelmilch, Amanda
More than 20 Community Conversations were held with the goal of increasing inclusive school and employment opportunities for youth with disabilities between the spring of 2011 and spring of 2016. Approximately 700 citizens of a large Midwestern state participated, including teachers, parents, students, school administrators, adult service providers, vocational rehabilitation counselors, representatives from postsecondary education institutions, policy makers, and employers. Valuable stakeholder input, including ideas for increasing integrated employment outcomes, was generated. Data obtained, including sample questions, are summarized. The plethora of ideas and action steps developed at these events is described, along with perspectives shared by specific stakeholders. In addition, survey responses were obtained at a portion of the Community Conversations to determine level of belief among stakeholders that students with significant disabilities can work in the community and to gauge perceived values of the Community Conversation process itself. Raised employment expectations were seen, and numerous examples of rapid engagement of employers, students, teachers, and family members occurred. For multiple students, new employment opportunities were developed as a direct result of a Community Conversation.